Effects of isolated or combined carbohydrate and caffeine supplementation on tennis training performance: single-blind randomized placebo-controlled crossover session - Abdioglu, Mekki; Mor, Ahmet; Alexe, Dan Iulian; Todor, Raul Marian; Adelina Panaet, Elena; Alexe, Cristina Ioana; Akca, Firat (Frontiers in Nutrition, 2025)
BackgroundIn long tennis matches, the number of unforced errors in groundstrokes increases. However, players need to maintain their successful strokes consistently in order to be successful in matches. To overcome this situation, tennis players utilize certain ergogenic supplements. In order to determine the most effective ergogenic supplement on players’ performance, it is aimed to investigate the effects of caffeinated chewing gum (CAFGUM), carbohydrate gel (CHOGEL) and cho gel + cafe gum (CHOGEL + CAFGUM) on tennis players’ basic strokes, countermovement jumps (CMJ), heart rate (HR), ratings of perceived exertion (RPE) and gastrointestinal discomfort in a training session.MethodThe study included 14 male tennis players (mean age: 15.93 ± 0.83 years, height: 173.86 ± 6.89 cm, and body mass: 60.64 ± 2.58 kg) with experience in national and international tournaments. Players ingested CHOGEL (21.1 g) + CAFGUM (100 mg) or CHOGEL (21.1 g) + gum placebo (PLAGUM) or CAFGUM (100 mg) or PLAGUM before a high-intensity workout and at the end of each set.ResultsThe CHOGEL + CAFGUM session performed better groundstrokes than the control (CON) (p = 0.001) and the PLAGUM sessions (p = 0.001). When total RPE values were considered in the training session, the CHOGEL + CAFGUM session had lower RPE scores than the CON (p = 0.010) and PLAGUM (p = 0.044) sessions. The CHOGEL + PLAGUM session had significantly lower RPE scores than the CON (p = 0.005) and PLAGUM (p = 0.005) sessions. The CAFGUM session had significantly lower RPE scores than the CON (p = 0.013). It was observed that no supplements significantly affected either HR (p = 0.188) or CMJ (p = 0.349) scores.ConclusionsIn conclusion, there was a significant difference on basic strokes and RPE scores between CHOGEL + CAFGUM supplementation used before and during training compared with the control session. At the same time, there was no significant performance outcomes between CHOGEL and CAFGUM sessions.